2020
DOI: 10.3310/hta24430
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for adults with a history of complex traumatic events: the INCiTE mixed-methods systematic review

Abstract: Background People with a history of complex traumatic events typically experience trauma and stressor disorders and additional mental comorbidities. It is not known if existing evidence-based treatments are effective and acceptable for this group of people. Objective To identify candidate psychological and non-pharmacological treatments for future research. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 431 publications
1
7
0
Order By: Relevance
“…The meta‐analysis indicates that TIC was more effective than usual care for women experiencing IPV in reducing psychological problems such as PTSD, depression and anxiety measured at three and 6 months after treatment. This review shows evidence that TIC can improve psychological symptoms in women experiencing IPV, which is line with previous reviews (Coventry et al, 2020; Hameed et al, 2020; Han et al, 2021; Melton et al, 2020; Weber et al, 2021). However, no statistically significant difference was observed in PTSD after 3 and 6 months of treatment.…”
Section: Discussionsupporting
confidence: 90%
“…The meta‐analysis indicates that TIC was more effective than usual care for women experiencing IPV in reducing psychological problems such as PTSD, depression and anxiety measured at three and 6 months after treatment. This review shows evidence that TIC can improve psychological symptoms in women experiencing IPV, which is line with previous reviews (Coventry et al, 2020; Hameed et al, 2020; Han et al, 2021; Melton et al, 2020; Weber et al, 2021). However, no statistically significant difference was observed in PTSD after 3 and 6 months of treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Higher use of antipsychotics in refugees than in their Swedish-born counterparts was observed, contrary to a general tendency of the Swedish-born showing higher medication use than refugees in most of the other considered medication categories. Antipsychotic medications are used not only as a first-line treatment for psychosis, such as schizophrenia but also in combination with selective serotonin reuptake inhibitors (SSRIs) to treat post-traumatic stress disorder (PTSD) [ 29 31 ]. A previous study examining the psychiatric utilization among refugee, non-refugee migrants, and Swedish-born youth also suggested higher use of psychiatric care among refugees due to PTSD [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vasilica et al [39] reported creating a web-based network to co-design a social media-based platform with the aim of generating information to improve disease outcomes [39]. In addition, web-based platforms through a web-based voting system have been used for establishing research priorities [133].…”
Section: Digital Methods To Promote Ppimentioning
confidence: 99%